Biodegradation of bilge water: Batch test under anaerobic and aerobic conditions and performance of three pilot aerobic Moving Bed Biofilm Reactors (MBBRs) at different ﬁlling fractions - Vyrides, Ioannis; Drakou, Efi Maria; Ioannou, Stavros; Michael, Fotoula; Gatidou, Georgia; Stasinakis, Athanasios S. (My University, 2018)
The bilge water that is stored at the bottom of the ships is saline and greasy wastewater with a high Chemical Oxygen Demand (COD) fluctuations (2–12 g COD L−1). The aim of this study was to examine at a laboratory scale the biodegradation of bilge water using first anaerobic granular sludge followed by aerobic microbial consortium (consisted of 5 strains) and vice versa and then based on this to implement a pilot scale study. Batch results showed that granular sludge and aerobic consortium can remove up to 28% of COD in 13 days and 65% of COD removal in 4 days, respectively. The post treatment of anaerobic and aerobic effluent with aerobic consortium and granular sludge resulted in further 35% and 5% COD removal, respectively. The addition of glycine betaine or nitrates to the aerobic consortium did not enhance significantly its ability to remove COD from bilge water. The aerobic microbial consortium was inoculated in 3 pilot (200 L) Moving Bed Biofilm Reactors (MBBRs) under filling fractions of 10%, 20% and 40% and treated real bilge water for 165 days under 36 h HRT. The MBBR with a filling fraction of 40% resulted in the highest COD decrease (60%) compared to the operation of the MBBRs with a filling fraction of 10% and 20%. GC-MS analysis on 165 day pointed out the main organic compounds presence in the influent and in the MBBR (10% filling fraction) effluent.
Keywords: Bilge water; Anaerobic granular sludge; Glycine betaine; Microbial consortium; Post treatment; Moving Bed Biofilm Reactor (MBBR)